Parental caringscapes – the analyses of mothering practices in local community contexts - Nagy, Éva; Horkai, Anita (Acta Medicinae et Sociologica, 2021)
During the last two decades of Family Sociology there is a growing interest toward understanding the complex phenomenon of parental experience. According to the changing perspective of the field, parental experience is embracing three different but interrelated aspects: the parenthood as a social institution, practices and agency of parenting and the intimate relationship between a particular child and her/his parent. This approach reflects to the changing social interpretations of parenthood and the growing emphasize on the “good parenting” in lay and professional discourses, and diversification of institutional and informal contexts of parental care. As a part of this process the status that parents occupy in different social fields shows diversity as well, and sometimes parents experience distance between the value of their parental status in varying contexts. Becoming a new mother can lead to central position in the family, while on the societal level it may goes together with a kind of isolation and the feeling of periphery. This gap has an effect on evaluation of parental competencies, autonomy and parental interpretations of care. In our study implementing a human geographic approach we suggest that parental care and the relating experiences cannot be separated from the wider and narrower space, place and time where the actual caring work is occurring.